Measurement of the branching fraction for B-+/-->chi K-c0(+/-) - Aubert, B; Barate, R; Boutigny, D; Gaillard, J; Hicheur, A; Karyotakis, Y; Lees, J; Robbe, P; Tisserand, V; Zghiche, A; Palano, A; Pompili, A; et al. (2004)
We present a measurement of the branching fraction of the decay B ±→χc0K± sample of 89×106 BB̄ pairs collected by the BABAR detector at the SLAC PEP-II asymmetric-energy B factory. The χc0 meson is reconstructed through its two-body decays toπ+ π- and K+K-. We measure B(B± → χc0K±) ×Β(χ c0→π+π-) = [1.32-027+0.28(stat)±0.26(syst)] × 10-6 and B(B ±→ χc0K±) × B(χc0 →K+K-) = [1.49 -0.34+0.36(stat) ±0.22(syst)] × 10 -6. Using the known values for the χc0 decays branching fractions, we combine these results to obtain Β(B ± →χc0K±) = (2.7±0.7)× 10-4. © 2004 The American Physical Society.